Potentiality of Solanum torvum as an agent of feminization Anabas testudineus Bloch 1792: a Review - Rahmania, Wanda; Baihaqi, Ahmad Uzair; Heryanto, Heryanto; Handajani, Hany (Journal Omni-Akuatika, 2022)
Climbing perch (Anabas testudineus) has a high economic value. Females grow faster than males. Sex reversal is one of genetic engineering by manipulating their hormone that is able to change the phenotype from male to female or vice versa. "Cepoka" eggplant (Solanum torvum) has been known as a medicinal and kitchen ingredient. Phytochemical test on S. torvum showed revealed that this plant contains tannins, saponins, flavonoids, steroids, alkaloids and terpenoids. Solasodine is a steroidial glycoalkaloid compound contained in S. torvum which has anti-fertility effects. Besides solasodine, the content of Gosipol in phenol compounds with BM 518.55 Dalton also has been known to be able to inhibit spermatogenesis by reducing the concentration, motility and viability of spermatozoa. The solasodine contained in S. torvum has the potential to be used for sex transfer in A. testudineus. Based on many studies, the utilize of solasodine from S. torvum could decrease the motility of spermatozoa. Even the results of the histological test on spermatogenesis, S. torvum gave a positive trend in inhibiting tilapia testicular cells in microscopic observation. Based on it, the chances of successful feminization of S. torvum utilizing cepoka eggplant are very high. A factor that must be considered in feminization is the age of the larvae, immersion dosige, immersion time and environment.Key Words : eggplant, Climbing perch, sex reversal, spermatozoa, solasodine